2021
DOI: 10.1038/s41598-021-00470-9
|View full text |Cite
|
Sign up to set email alerts
|

Passively driven microfluidic device with simple operation in the development of nanolitre droplet assay in nucleic acid detection

Abstract: Since nucleic acid amplification technology has become a vital tool for disease diagnosis, the development of precise applied nucleic acid detection technologies in point-of care testing (POCT) has become more significant. The microfluidic-based nucleic acid detection platform offers a great opportunity for on-site diagnosis efficiency, and the system is aimed at user-friendly access. Herein, we demonstrate a microfluidic system with simple operation that provides reliable nucleic acid results from 18 uniform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…There was a visible increase in the concatemeric signal intensity as the Ct value decreased, corresponding to the higher viral load in the sample. The gel electrophoresis result showed that RT-LAMP could amplify swab samples with the highest (33) and lowest (18.55) Ct values within 20 min of processing time at 65 • C.…”
Section: Optimisation Of Processing Times For Swab Sample Amplificati...mentioning
confidence: 99%
“…There was a visible increase in the concatemeric signal intensity as the Ct value decreased, corresponding to the higher viral load in the sample. The gel electrophoresis result showed that RT-LAMP could amplify swab samples with the highest (33) and lowest (18.55) Ct values within 20 min of processing time at 65 • C.…”
Section: Optimisation Of Processing Times For Swab Sample Amplificati...mentioning
confidence: 99%
“…Among all water contamination, heavy metal ions such as Pb(II), Cd(II), Zn(II), Ni(II) and Hg(II) are highly toxic and non-biodegradable, potentially causing serious health problems in animals. and humans (P. H. Lin & Li, 2021;Shari et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics is multidisciplinary for precise regulation and manipulation in geometrically confined small-scale fluids (22). Microfluidics has practical applications, such as cell size sorting, particle formation, particle trapping, and gradient generation, and is widely applied in the fields of organs-on-chip, cell culture, drug delivery, biochemistry, and biotechnology (23)(24)(25). Microfluidics offers great opportunities for integration with wearable sensors that complete the sample-to-answer solution (26).…”
Section: Introductionmentioning
confidence: 99%